The Modified Ampullar Approach for Vestibular Implant Surgery: Feasibility and Its First Application in a Human with a Long-Term Vestibular Loss - Van De Berg, Raymond; Guinand, Nils; GUYOT, Jean-Philippe; Kingma, Herman; Stokroos, Robert (Frontiers in Neurology, 2012)
Objective: To assess, for the first time in a human with a long-term vestibular loss, a modified approach to the ampullae and the feasibility of evoking a VOR by ampullar stimulation. Material and methods: Peroperative stimulation of the ampullae, using the ampullar approach, was performed under full anaesthesia during cochlear implantation in a 21-year old female patient, who had experienced bilateral vestibular areflexia and sensorineural hearing loss for almost twenty years. Results: The modified ampullar approach was performed successfully with as minimally invasive surgery as possible. Ampullar stimulation evoked eye movements containing vectors congruent with the stimulated canal. As expected, the preliminary electrophysiological data were influenced by the general anaesthesia, which resulted in current spread and reduced maximum amplitudes of eye movement. Nevertheless, they confirm the feasibility of ampullar stimulation. Conclusion: The modified ampullar approach provides safe access to the ampullae using as minimally invasive surgery as possible. For the first time in a human with long-term bilateral vestibular areflexia, it is shown that the VOR can be evoked by ampullar stimulation, even when there has been no vestibular function for almost twenty years. This approach should be considered in vestibular surgery, as it provides safe access to one of the most favourable stimulus locations for development of a vestibular implant.